ANALISIS KELAYAKAN FINANSIAL DAN EFISIENSI PEMASARAN LADA DI KECAMATAN GUNUNG LABUHAN KABUPATEN WAY KANAN - Ade Lia Delita; Fembriarti Erry Prasmatiwi; Helvi Yanfika (Lampung University, 2015)
The research aims to find out: financial feasibility of pepper farming and marketing efficiency of pepper. This research was conducted in two pepper production centers, Gunung Labuhan Village and Bengkulu Tengah Village, Gunung Labuhan Subdistrict of Way Kanan Regency. Respondents consisted of fifty pepper farmers selected randomly by using stratified random sampling and six pepper traders determined by using snowball sampling. The first goal was analyzed using investment criteria and sensitivity rate. The second goal was analyzed using marketing margins, price correlations, and price transmission elasticity. The results showed that pepper farming is worth to attempt based on the value of investment criteria and the sensitivity rate analysis against changes that may occur. The changes were the production cost increase of 8.38% the production quantity decrease of 30%, and the production price decrease of 13 %. The market structure was oligopsonistic market with the price correlation coefficient value of 0.47, which means pepper market is not perfectly competitive, and price transmission elasticity value of 1.74, which means the rate of change in consumer prices is greater than the rate of change in producer prices. Key words : feasibility, financial,marketing, pepper